Adequate Access to Contraception and Sexual and Reproductive Health (SRH) Information Post-Abortion: A Case Study from Nepal - Rogers, Claire Ellen (Curtin University, 2018)
This qualitative, exploratory study examined the post-abortion experiences of Nepali women, and access and uptake of safe abortion services; unsafe abortion; post-abortion contraception; and sexual and reproductive health information. Analysis revealed themes relating to women’s abortion seeking decision-making processes and barriers to high quality safe abortion services and family planning counselling. Findings emphasised the interconnectivity of sexual and reproductive health and rights; gender discrimination, reproductive coercion; education; poverty; geographical isolation; spousal separation; and women’s empowerment.